2020
DOI: 10.1111/ocr.12454
|View full text |Cite
|
Sign up to set email alerts
|

The relation of cephalometric features to internal derangements of the temporomandibular joint: A systematic review and meta‐analysis of observational studies

Abstract: Temporomandibular disorder (TMD) is a clinical syndrome with a considerable prevalence and ambiguous pathogenesis. [1][2][3][4][5] Internal derangement (ID) of the temporomandibular joint (TMJ) includes several abnormal positions of the disc in the condyle and articular eminence, 6 which are all regarded as subtypes of TMD according to the Diagnostic criteria for TMD (DC/TMD), 7 and it is detected in 70% of patients with TMD. 8 To the best of our knowledge, several reasons, including physical, psychological, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Among the vertical relationship measurements, an insufficient posterior facial height and steeper mandibular plane angle were observed in the DD groups, in line with the previous literature [ 11 ]. The trend was more pronounced in the DDwoR group compared with the DDwR group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among the vertical relationship measurements, an insufficient posterior facial height and steeper mandibular plane angle were observed in the DD groups, in line with the previous literature [ 11 ]. The trend was more pronounced in the DDwoR group compared with the DDwR group.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies have underlined the potential correlations between craniofacial morphology and different disc positions in TMD patients [ 9 , 10 ]. A retrusion and clockwise rotation of the mandible, smaller ramus height and decreased posterior facial height have been reported as remarkable morphological features in DD patients [ 11 ]. However, insufficient attention has been paid to potential confounding factors, such as age, sex, ancestry or environment, which are possible risk factors for TMDs as well as significant determinants in the formation of different craniofacial morphologies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shu et al [ 17 ] conducted a systematic review, in which they concluded that especially the size (smaller ramus height, short mandible) and position (clockwise rotation, retruded position) of the mandible were strongly associated with the presence of TMJ internal derangements.…”
Section: Discussionmentioning
confidence: 99%
“…TMJ internal derangements have been found to be associated with some changes in the morphology of the mandible, including retruded position of the mandible, decreased ramus height and clockwise rotation of the mandible (on the sagittal plane) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shu et al 347 sought information on the relationship between cephalometric features and internal derangements (IDs) of the TMJs. A systematic review was designed, and PubMed, Embase, and Scopus databases were searched for cephalometric studies comparing the craniofacial morphology between women with TMJ-ID and controls.…”
Section: Growth and Developmentmentioning
confidence: 99%